In honour of R.C.B. Risk - Risk, R. C. B., 1936-; Baker, G. Blaine; Phillips, Jim, 1954- (Essays in the history of Canadian law, 1999)
The collected essays in this volume represent the highlights of legal historical scholarship in Canada today. All of the essays refer back in some form to Risk's own work in the field.